Impact of tafamidis on myocardial strain in transthyretin amyloid cardiomyopathy. (2nd January 2023) - Rettl, René; Duca, Franz; Binder, Christina; Dachs, Theresa-Marie; Cherouny, Bernhard; Camuz Ligios, Luciana; Mann, Christopher; Schrutka, Lore; Dalos, Daniel; Charwat-Resl, Silvia; Badr Eslam, Roza; Kastner, Johannes; et al.
Abstract: Aims: The impact of tafamidis on myocardial strain in patients with transthyretin amyloid cardiomyopathy (ATTR-CM) have been barely investigated. We aimed to determine tafamidis-induced changes using serial speckle tracking echocardiography and to identify imaging parameters for specific therapy monitoring. Methods and results: ATTR-CM patients underwent serial TTE with two-dimensional (2 D) speckle tracking imaging. Patients receiving tafamidis free acid 61 mg ( n  = 62) or tafamidis meglumine 20 mg ( n  = 21) once daily (QD) showed stable measurements at follow-up (61 mg: 8.5 months, 20 mg: 7.0 months) in LV global longitudinal strain (GLS) (61 mg: −11.75% vs. −11.58%, p  = 0.534; 20 mg: −10.61% vs. −10.12%, p  = 0.309), right ventricular (RV) GLS (61 mg: −14.18% vs. −13.72%, p  = 0.377; 20 mg: −14.53% vs. −13.99%, p  = 0.452) and left atrial (LA) reservoir strain (LASr; 61 mg: 8.80% vs. 9.42%, p  = 0.283; 20 mg: 8.23% vs. 8.67%, p  = 0.589), whereas treatment-naïve ATTR-CM patients ( n  = 54) had clear signs of disease progression at the end of the observation period (10.5 months; LV-GLS: −11.71% vs. −10.59%, p  = 0.001; RV-GLS: −14.36% vs. −12.99%, p  = 0.038; LASr: 10.67% vs. 8.41%, p  = 0.005). Between-group comparison at follow-up revealed beneficial effects of tafamidis free acid 61 mg on LASr ( p  = 0.003) and the LV (LV-GLS: p  = 0.030, interventricular septum (IVS): p  = 0.006), resulting in clinical benefits (six-minute walk distance (6-MWD): p  = 0.006, NT-proBNP: p= <0.001), while patients treated with tafamidis meglumine 20 mg QD showed positive effects on LASr ( p  = 0.039), but no differences with respect to the LV (LV-GLS: p  = 0.274, IVS: p  = 0.068) and clinical status (6-MWD: p  = 0.124, NT-proBNP: p  = 0.053) compared to the natural course. Conclusions: Treatment with tafamidis free acid 61 mg in ATTR-CM patients delays the deterioration of LA and LV longitudinal function, resulting in significant clinical benefits compared with natural history. Serial TTE with 2 D speckle tracking imaging may be appropriate for disease-specific therapy monitoring.